2018
DOI: 10.1128/aem.01113-18
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Acetylation System in Vibrio cholerae Modulates Virulence in Arthropod Hosts

Abstract: Acetylation is a broadly conserved mechanism of covalently modifying the proteome to precisely control protein activity. In bacteria, central metabolic enzymes and regulatory proteins, including those involved in virulence, can be targeted for acetylation. In this study, we directly link a putative acetylation system to metabolite-dependent virulence in the pathogen We demonstrate that the and genes, which encode homologs of a deacetylase and an acetyltransferase, respectively, modulate metabolism of acetate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…This finding suggests that CsrA may exert large regulatory effects on the V. cholerae transcriptome by controlling the expression of other regulators. Consistent with our observation that CsrA is required for virulence within the host, we identified multiple CsrA-interacting mRNAs associated with pathogenesis, including the following: aphA (26); flrC (27); epsC, which encodes a component of the type two secretion system that is responsible for the secretion of the cholera toxin (28); cobB, which encodes an NAD1 dependent deacetylase (29); and VCA0965, encoding a functional cyclic di-GMP synthase (30). Selected regulators are discussed in more detail below.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…This finding suggests that CsrA may exert large regulatory effects on the V. cholerae transcriptome by controlling the expression of other regulators. Consistent with our observation that CsrA is required for virulence within the host, we identified multiple CsrA-interacting mRNAs associated with pathogenesis, including the following: aphA (26); flrC (27); epsC, which encodes a component of the type two secretion system that is responsible for the secretion of the cholera toxin (28); cobB, which encodes an NAD1 dependent deacetylase (29); and VCA0965, encoding a functional cyclic di-GMP synthase (30). Selected regulators are discussed in more detail below.…”
Section: Resultssupporting
confidence: 80%
“…The acetate switch promotes the transition from acetate excretion during rapid growth to acetate assimilation when other, preferred, carbon sources become depleted. Expression of genes involved in the acetate switch, including genes encoding the two-component system CrbRS (VC0303/VC2702), a putative cation-acetate symporter system (VC2704/VC2705), acetyl-CoA synthase (VC0298) (50), and CobB (VC1509), which activates the acetyl-CoA synthase through deacetylation (29), was reduced in the csrA mutant at stationary phase, consistent with positive regulation of these genes by CsrA. Although the statistical threshold for inclusion in the data set (P , 0.05) was not met in every case for these genes, the overall trend in gene expression suggests that V. cholerae is no longer excreting acetate via glycolysis and mixed acid fermentation in stationary phase, but is instead taking up acetate from the medium and using it in the TCA cycle in a CsrA-dependent process.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This Pat protein contains a regulatory domain of unknown function (~700 amino acids) attached to the catalytic GNAT domain (~200 amino acids). Recent work also highlights the importance of Acs acetylation and deacetylation during bacterial infections (44). Using Vibrio cholerae and Drosophila melanogaster as an infection model, it was found that dysregulation of Acs acetylation reduced V. cholera virulence.…”
Section: Cellular Processes Under Reversible Lysine Acetylation Controlmentioning
confidence: 99%
“…Using Vibrio cholerae and Drosophila melanogaster as an infection model, it was found that dysregulation of Acs acetylation reduced V. cholera virulence. This work emphasizes the impact of protein acetylation on the physiology of pathogenic bacteria that affect human health across the world (44). While many studies characterizing Acs acetylation by Pat have similarities, there are also differences worth discussing here.…”
Section: Cellular Processes Under Reversible Lysine Acetylation Controlmentioning
confidence: 99%
“…YfiQ is a conserved acetyltransferase (12) with homologs found across many bacterial species, including E. coli (69), Vibrio cholerae (5), Salmonella enterica (70), Yersinia pestis (10), Rhodopseudomonas palustris (71), Streptomyces lividans (72), and Streptomyces griseus (73). The best-understood role for YfiQ is acetylation of acetyl-CoA synthetase (Acs); acetylation inactivates Acs, preventing acetate consumption (70).…”
Section: Introductionmentioning
confidence: 99%